MAKNA DENOTASI DAN KONOTASI DALAM NASKAH FILM THE MENU KARYA MARK MYLOD - Pelleng, Jennifer Bianca; Ranuntu, Garryn C.; Sebayang, F. Ari Anggraini (Universitas Sam Ratulangi, 2026)
This research is entitled “Denotative and Connotative Meanings in the Script of the Film The Menu by Mark Mylod (Semantic Analysis)”. This research examines the denotative and connotative meanings found in the script of the film The Menu by Mark Mylod. The aim of this research is to identify, classify and analyze the meaning of denotation and connotation found in the movie script The Menu by Mark Mylod. The theory used in this research was the theory of Geoffrey Leech (1981). The writer used a qualitative descriptive method to collect data in this research. The writer identified and classified words, phrases and sentences then analyzed the meaning of denotation and connotation. The study finds, there are 33 data, consist of 20(words), 10(phrase) and 3(sentences), which contains denotative and connotative meaning. The connotative meaning contained in the movie script for The Menu by Mark Mylod has an important meaning and message for readers or viewers. The writer finds that the meaning of denotation and connotation is not only found in scripts or films but can also be found in everyday life and in relation to each other.